PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) DI BAGIAN PENYIMPANAN REKAM MEDIS RUMAH SAKIT UMUM DAERAH X BANDUNG - Amelian, Yudo Sri Valeri Sri Valeri; Johan, Ade (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2024)
Occupational safety and health can support the performance of officers during work, especially in medical record filing. Improperly implemented occupational safety and health causes work accidents. The purpose of occupational health and safety is to prevent, reduce, protect and even eliminate the risk of work accidents. Therefore, it is necessary to conduct research on occupational safety and health in Medical Record Filing. This study aims to reveal the implementation of occupational safety and health in Medical Record filing section in Hospital X. This research method uses a qualitative approach with a descriptive method. Interview and observation were used as data collection techniques. The subjects in this study were 8 medical record filing officers and 1 medical record filing room at Hospital X. The result showed that filing staff did not use personal protective equipment completely, the air temperature of filing room did not meet the threshold value, there were still disease vectors, the medical record filing room was dusty, there was no ventilation, and staff had work-related health problems such as dry cough and itching. Researchers suggest the efforts in socializing the importance of occupational safety and health (K3), adding personal protective equipment, adding air conditioners, buying vacuum cleaners, adding ventilation, windows or doors, maintaining cleanliness and completely applying K3 principles.